Peran Kebijakan Kurikulum Merdeka Terhadap Kesiapan Guru dan Hasil Belajar Peserta Didik - Z, Zulqaidah; Harahap, Hasriyati; Tanjung, Rama Satya; Dermawan, M. Muflih; Darmansah, Tengku (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2024)
As a new policy, the implementation of the Independent Curriculum brings big challenges, especially in terms of teacher readiness to face it. Teacher readiness, both in terms of professional competence and ability to use technology in learning, is the key to the successful implementation of this curriculum. This research uses the literature review method. Literature review is a research method for identifying, evaluating and interpreting all relevant research results related to certain research questions, certain topics, or phenomena of concern. The aim of this research is to explore the role of the Independent Curriculum policy on teachers' readiness to implement it and its impact on student learning outcomes, Basic Concepts of the Independent Curriculum Policy, Teacher Readiness in Implementing the Independent Curriculum, Strategy for Developing Teacher Competence in the Independent Curriculum, Impact of the Independent Curriculum Policy on Learning Outcomes Students, Challenges and Solutions in Implementing the Independent Curriculum. The research results show that the implementation of this curriculum faces various challenges, especially related to teacher readiness. Teacher readiness, both in terms of professional competence and ability to use technology, is a key factor for successful curriculum implementation. This research emphasizes the importance of teacher capacity development programs, such as training and workshops, to increase learning effectiveness.